Performance Efficiency Improvement of Parabolic Solar Concentrating Collector (An Experimental Evaluation and Analysis) - Durai Kumar (Majlesi Journal of Electrical Engineering)
Energy conserved is energy generatedâ. Energy crisis is one of the crucial problems faced by all countries due to the rapid depletion of natural resources. A viable and an immediate solution at this juncture is the use of renewable energy sources like solar energy, wind energy, etc. A focusing type solar energy concentrator was fabricated and tested to evaluate its performance and to improve its operation efficiency. The experimental evaluations were carried out during the solar window (between 9:00 am to 3:00 pm) using the statistical solar irradiation data and the real time measurements carried out using a pyranometer. Efficiency improvement was tried through different reflecting surfaces, greenhouse effect and selective coating. The energy conservation, preservation of fossil fuel and carbon foot print were estimated along with the cost economics and presented in this article in a very simplified style.